Penitentiary Systems of CIS Countries in the Context of International Law: A Comparative Analysis of Implementation Practices - Mamyrbaev Р.Н.; Ayubaev М.А.; Sabitov С.М. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This article proposes for the first time a conceptualization of the penitentiary systems of CIS countries as a single "transitional model" for the implementation of international standards, situated between the Soviet penal paradigm and the modern human rights approach. A comparative matrix of the implementation of the provisions of the UN Committee against Torture and United Nations standards, including soft law instruments, has been developed, allowing for the identification of typical institutional gaps between international obligations and national practice. The relevance of this study lies in the fact that most CIS countries have formally ratified key international human rights treaties, including the International Covenant on Civil and Political Rights, the Convention against Torture, and its Optional Protocol. The purpose of this article is to conduct a comparative legal analysis of the practices of implementing international penitentiary standards in CIS countries, focusing on the Republic of Kazakhstan as a "transitional model." For the first time, the effectiveness of institutional mechanisms for implementing international standards has been quantitatively assessed using empirical data (NPM RK statistics, concluding observations of the UN Committee against Torture, and World Prison Brief data). This study revealed a gap between the number of monitoring visits (500+ per year) and the level of recommendation implementation (36.3%), confirming the thesis of "declarative implementation" in transitional models. The practical significance of this study lies in the potential use of the findings in further reforming the penal system of the Republic of Kazakhstan and improving the activities of national preventive mechanisms.